Using game engine for 3D terrain visualisation of GIS data: A review - Che Mat, Ruzinoor; Mohamed Shariff, Abdul Rashid; Zulkifli, Abdul Nasir; Rahim, Mohd Shafry Mohd; Mahayudin, Mohd Hafiz (IOP Publishing Ltd, 2014)
This paper reviews on the 3D terrain visualisation of GIS data using game engines that are available in the market as well as open source. 3D terrain visualisation is a technique used to visualise terrain information from GIS data such as a digital elevation model (DEM), triangular irregular network (TIN) and contour. Much research has been conducted to transform the 2D view of map to 3D. There are several terrain visualisation softwares that are available for free, which include Cesium, Hftool and Landserf.This review paper will help interested users to better understand the current state of art in 3D terrain visualisation of GIS data using game engines.